1980
DOI: 10.1152/jappl.1980.49.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Plasma testosterone during treadmill exercise

Abstract: Five male volunteers performed 20 min of steady-state submaximal exercise on a motor-driven treadmill at five intensities (30, 45, 60, 75, and 90% VO2 max) as well as several maximal aerobic capacity tests. Peripheral venous plasma testosterone concentrations increased above resting values in proportion to exercise intensity. However, this increase in plasma testosterone concentration was virtually equal in magnitude to the decrease in plasma volume observed consequent to the exercise bouts, resulting in no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…C and T reactions to athletic competition may be related through their shared connection to the psychological experience of athletic competition. In the athletic contests included in this report, competition-related increases in T are seen regardless of match or race outcome (Table 1) Both C and T in plasma increase during non-competitive aerobic exercise in proportion to the intensity and/or duration of the workout e.g., [25][26][27]. Softball is a sport which, unlike all the others studied here, does not involve a sustained period of physical exertion.…”
Section: Resultsmentioning
confidence: 85%
“…C and T reactions to athletic competition may be related through their shared connection to the psychological experience of athletic competition. In the athletic contests included in this report, competition-related increases in T are seen regardless of match or race outcome (Table 1) Both C and T in plasma increase during non-competitive aerobic exercise in proportion to the intensity and/or duration of the workout e.g., [25][26][27]. Softball is a sport which, unlike all the others studied here, does not involve a sustained period of physical exertion.…”
Section: Resultsmentioning
confidence: 85%
“…Similar to cortisol, testosterone levels increases linearly in response to physical exercise until a specific threshold of exercise intensity is reached, with peak concentrations generally occurring at the end of physical activity [32]. However, some studies have shown that there is a negative relationship between cortisol and testosterone under specific conditions.…”
Section: Testosterone/cortisol Ratio and The Stress Systemmentioning
confidence: 99%
“…With regards to an acute bout of endurance training, cortisol normally increases with respect to exercise intensity [104106], but the correlation is not necessarily linear [107]. Circulating cortisol concentrations have been demonstrated to increase in trained men after repeated 100m sprints [108] and increase in type 1 diabetics during and after sprinting exercises [109].…”
Section: Exercisementioning
confidence: 99%